Icing on the Cake: “Amplification Effect” of Innovative Information Form in News Reports About COVID-19 - Wen, Fangfang; Ye, Hanxue; Wang, Yang; Xu, Yian; Zuo, Bin (Frontiers in Psychology, 2021)
The outbreak of COVID-19 poses great challenges to the world economy and people’s daily lives. As a pandemic in the information age, the instant and diversified broadcasting of the pandemic situation has played an important role in stabilizing social mental state and avoiding inter-group conflicts. In order to explore the effects of innovative visual graphics in different news frames, the current study applied real-time and retrospective priming paradigm to examine the impacts of information frame (positive vs. negative) and form (traditional vs. innovative) on individuals’ risk perception, positive emotion, and willingness to help others during the outbreak and post-pandemic period in China. The results indicated inconsistent outcomes in the two paradigms: in real-time condition, information frame and form have significant interaction effects in their influences on risk perception, emotion, and willingness to help. Furthermore, the innovative form shows an “amplification effect,” which can amplify the power of the information frame. However, under the retrospective priming paradigm, the effects of information frame and form on risk perception and positive emotion were weakened, while the effects on willingness to help disappeared. In conclusion, the study provides evidences for the “amplification effect” of innovative information forms; that is, when data information is presented in graphic forms, the original positive/negative valence of it can be amplified. Besides, the comparison between two paradigms reveals the necessary background condition of the “amplification effect,” and also suggested the possible deviation of the retrospective paradigm in studies about disaster news. The findings of this study have important implications for the field of media psychology and social governance. It provides empirical support for the adjustment of public mental and behavioral conditions through changes in news reports during social crises.